ANALISIS LAPORAN KINERJA KEUANGAN PADA PT GARUDA INDONESIA (PERSERO), TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Bestari, Ismanur; Novalia, Nurkardina; Puspita, Santi (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the financial performance based on the value of the ratio of liquidity, solvency, activity, and profitability at PT. Garuda Indonesia Tbk, in improving financial performance by calculating the liquidity ratio with the current ratio and quick ratio, while the solvency ratio is the indicator of debt to assets and debt to equity ratio, the indicators of activity ratio are total assets turnover and inventory turnover, and indicators of profitability ratios are the return on investment and the return on equity. The secondary data was obtained by indirect data collection techniques that are documentation and literature study in the form of financial reports of PT. Garuda Indonesia Tbk which is listed on the Indonesia Stock Exchange (IDX) uses qualitative data analysis methods. The results of the analysis show that the liquidity ratio with the current ratio and the quick ratio in 2016-2020 does not meet industry standards. The solvency ratio in the debt to asset ratio in 2016-2020 does not meet industry standards. The activity ratio on total asset turnover in 2016-2020 meets industry standards and on inventory turnover in 20160-2020 meets industry standards. Finally, the ratio of profitability to return on investment in 2016-2020 does not meet industry standards. Keywords: Liquidity Ratio; Solvency; Activity; Profitability